The use of photoionization cross section for evaluating contribution of continuum to the blackbody radiation induced shift and broadening of Rydberg-state energy levels of group IIb ions. (April 2022) - Glukhov, I.L.; Kamenski, A.A.; Ovsiannikov, V.D.
Highlights: The quantitative data for contribution of continuum to Rydberg-state energy-level shift and broadening is determined for group IIb ions Asymptotic equations for the rates of the blackbody radiation (BBR) induced ionization and energy-level shifts are presented analytically in terms of Rydberg-states binding energy and photoionization cross section Quantitative analysis is given for angular-momentum dependence of photoionization cross section of Rydberg-state atoms and ions Analytic equations for amplitudes of bound-bound transitions from Rydberg states in the quantum defect approach are written in terms of generalized hypergeometric polynomials. Abstract: General properties of n -dependence at the threshold and regularities of above-threshold ionization cross sections for states with high principal quantum numbers n and arbitrary angular momenta l are determined and used for evaluating the blackbody-radiation(BBR)-induced ionization broadening of n S, n P, n D and n F Rydberg-state energy levels of the group IIb ions Zn +, Cd +, Hg + at temperatures from T = 100 K to T = 3000 K. The contributions to the energy level shifts from transitions into continuum are also determined with the use of the ionization cross sections. The single-electron quantum defect method (QDM) was used, which appears rather precise and suitable for calculating the amplitudes of radiation transitions from Rydberg states, and specifically for summation of matrix-element-dependent terms over infinite number of discrete states. The dependencies on temperature and binding energy are determined and approximate analytic equations are proposed for simplified evaluations of the BBR-induced ionization broadening and shifts. Numerical parameters of approximate equations are tabulated for S, P, D and F Rydberg states of the group IIb ions.